Maqāṣid al-Nabawī: Pendekatan Ilmu Maqāṣid al-Syarī’ah Dalam Kajian Hadis - Nursyahbani, Iqbal; Nurhamdani, Ahmad; Husen, Fahmi; Anang Firdaus, Mohammad (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2024)
One approach that can be used is the study of hadith with the approach of the science of maqāṣid al-syarī'ah. 'Abdullah bin Bayyah as one of the scholars who concentrates in the field of maqāṣid certainly has a theory that can be applied, especially his very well-accepted figure in the Eastern and Western worlds. This study aims to describe how the science of maqāṣid al-syarī'ah in the approach of 'Abdullāh bin Bayyah is used to understand the hadith of the Prophet, as well as simple applications that can be carried out. The method used by the researcher is qualitative with the type of library research that makes the book Masyāhid min al-Maqāṣid the main data source, which is then supported by other data sources. The application that the researcher does is on the study of the hadith about seeking treatment with ḥabbat al-saudā'. The research results reveal that after being studied with the maqāṣid approach, the hadith of ḥabbat al-saudā' has the understanding that the main purpose of the hadith is the command to protect oneself or ḥifẓ al-nafs by seeking treatment, and the derivative purpose is that protecting oneself can be done by seeking treatment, resting, eating and drinking nutritious food, exercising, and all things that are in accordance with the needs of each individual for himself. This is because the hadith is general in nature and the Prophet said it based on observations of one of the companions who was sick, then he recommended that medicine.